PEMBINGKAIAN SEKSUALITAS ANAK PADA VIDEO MUSIK HEAVY ROTATION OLEH GRUP IDOL AKB48 MENGGUNAKAN MODEL FRAMING GAMSON DAN MONDIGLIANI - Fajriannoor Fanani; Errika Dwi Setya Watie (Cakrawala Jurnal Penelitian Sosial, 2020)
The launch of the Heavy Rotation Music Video by Japanese Idol Group AKB48 has sparked debate among fans of the Idol Group. This Music Video is considered to have sexually exploited the members of the Idol Group, most of whom are still teenagers. This research was conducted to find out whether the music video really features these sexual aspects. This research was conducted qualitatively using Gamson and Mondigliani framing analysis. The research was conducted by observing the lyrics to the audio visual appearance in the music video. The results of this study indicate that the music video producer did strongly highlight the sexual aspects of AKB48 members. The protrusion is carried out in such a way in the visual image device that there is almost no relationship between the lyrics and the audio visual display. The prominence of sexuality is also unique because it also highlights the cuteness of AKB48 members. This is in accordance with the trend of the Japanese entertainment industry which likes the concept of kawaii where entertainment objects are displayed cute, attractive, helpless, shy, and childish.